2019
DOI: 10.3390/vetsci6010034
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for p53 and p16CDKN2A Protein Is Not Predictive of Prognosis for Dogs with Malignant Mammary Gland Neoplasms

Abstract: Mammary gland tumors (MGTs) are common in dogs and show a variable clinical behavior that is difficult to predict. Currently, few immunohistochemical markers have been established to predict the prognosis of a canine MGT. However, p53 immunostaining has been variably reported to be prognostic for canine MGTs. Additionally, while p16CDK2NA protein (p16) immunostaining has been found to be prognostic for human breast cancers, this marker has never been evaluated as a prognostic marker for canine neoplasms. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Mutations in the p53 gene are associated with more than half of all human cancers and have been described in multiple cancers in dogs ( 196 ), including mammary tumors ( 197 , 198 ). However, its expression and mutation status as prognostic factors in veterinary medicine are controversial: while some studies have found no correlation ( 199 , 200 ), other authors have associated higher levels of p 53 with poor overall survival ( 201 , 202 ).…”
Section: Adjuvant Targeted Therapiesmentioning
confidence: 99%
“…Mutations in the p53 gene are associated with more than half of all human cancers and have been described in multiple cancers in dogs ( 196 ), including mammary tumors ( 197 , 198 ). However, its expression and mutation status as prognostic factors in veterinary medicine are controversial: while some studies have found no correlation ( 199 , 200 ), other authors have associated higher levels of p 53 with poor overall survival ( 201 , 202 ).…”
Section: Adjuvant Targeted Therapiesmentioning
confidence: 99%
“…Previous studies have investigated the expression of p53 in CMTs by PCR (polymerase chain reaction) and/or immunohistochemistry, but its association with prognosis and malignancy is still controversial. 5,16,17,22 Earlier research found that p53-positive status was significantly related to poor tumor differentiation, higher mitotic count, invasive growth, and necrosis. 5,31 However, other studies on TP53 gene expression found that its expression profile could not be considered a marker for tumor aggressiveness in CMTs.…”
mentioning
confidence: 99%
“…In the canine species, for which many studies are based on immunohistochemistry alone, altered p53 immunoexpression has been reported in different tumors, such as cutaneous hemangiosarcomas [12,13], mammary carcinomas [13][14][15], osteosarcomas [2,[16][17][18], liposarcomas [19], mast cell tumors [20], squamous cell carcinomas [21], transmissible venereal tumors [22], prostate cancer [23], and epithelial colorectal tumors [24]. Different monoclonal and polyclonal antibodies were used in these studies, and they had conflicting results in terms of both the extent of positivity and the correlation with prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in both human and veterinary medicine [14,19,26], a 10% cutoff for nuclear immunopositivity is used, but as there is disagreement among authors, where several cutoff values have been used for both humans [1,7] and dogs [12,15,18,27].…”
Section: Introductionmentioning
confidence: 99%